Perceptions of face threats in conflict. Issue 3 (20th January 2022) - Donohue, William A.; Druckman, Daniel
Abstract : Purpose: The purpose of this study was to determine the relative impact of positive and negative face threats in conflict scenarios on the relational quality between disputants. This study also sought to determine whether the contextual variables of relational distance and power differential mediated this relationship as predicted by politeness theory. Design/methodology/approach: To test the hypotheses, a 2 × 2 × 2 design was implemented manipulating the variables face (positive and negative), relational distance (business and personal) and power differential (high and low power differential). Participants read one of the eight scenarios, then responded to the dependent variables which focused on the impact of the face threats on relational quality between the participants. Subjects were recruited using the M-Turk, Amazon platform. Manipulation checks were carefully constructed to ensure subjects understood them. Findings: The results of this study indicated that positive face threats have significantly more impact on relational quality between disputants than negative face threats. Moreover, context did not mediate these results. Neither relational distance nor power differential impacted the extent to which positive face threats compromised the relationship between the disputants. Research limitations/implications: This is the first study to explore the impact of face threats on relational outcomes in conflict. Prior studies focused only on the extent to which contextual variables would impact the choice of face threats that disputants might make in response to power and relational distance differences. This result suggests that face threats play a significant role in determining relational outcomes in conflict settings. Practical implications: This study suggests that practitioners, such as mediators or group facilitators, should take steps to limit the kinds of positive face threats that disputants exchange during conflict. If positive face threats are allowed to escalate, then they can severely compromise the willingness of disputants to trust and continue to work toward an integrative solution. Social implications: Political divisions often appear to widen in the context of positive face threats as individuals seek to belittle the identities of their opponents. As these face threats escalate, they can result in polarizing language that disempowers these individuals from wanting to work together in a trusting relationship to accomplish important social goals. Originality/value: This is the first study to explore the relative impact of positive and negative face threats on the relational quality of disputants in conflict. It is also the first to explore the extent to which context mediates the impact of face threats.